Outlining Core Pathways of Amyloid Toxicity in Bacteria with the RepA-WH1 Prionoid - Molina-García, Laura; Moreno-del Álamo, María; Botias, Pedro; Martín-Moldes, Zaira; Fernández, María; Sánchez-Gorostiaga, Alicia; Alonso-del Valle, Aída; Nogales, Juan; García-Cantalejo, Jesús; Giraldo, Rafael (Frontiers in Microbiology, 2017)
The synthetic bacterial prionoid RepA-WH1 causes a vertically transmissible amyloid proteinopathy in Escherichia coli that inhibits growth and eventually kills the cells. Recent in vitro studies show that RepA-WH1 builds pores through model lipid membranes, suggesting a possible mechanism for bacterial cell death. By comparing acutely (A31V) and mildly (ΔN37) cytotoxic mutant variants of the protein, we report here that RepA-WH1(A31V) expression decreases the intracellular osmotic pressure and compromise bacterial viability under either aerobic or anaerobic conditions. Both are effects expected from threatening membrane integrity and are in agreement with findings on the impairment by RepA-WH1(A31V) of the proton motive force (PMF)-dependent transport of ions (Fe3+) and ATP1 synthesis. Systems approaches reveal that, in aerobiosis, the PMF-independent respiratory dehydrogenase NdhII is induced in response to the reduction in intracellular levels of iron. While NdhII is known to generate H2O2 as a by-product of the autoxidation of its FAD cofactor, key proteins in the defense against oxidative stress (OxyR, KatE), together with other stress-resistance factors, are sequestered by co-aggregation with the RepA-WH1(A31V) amyloid. Our findings suggest a route for RepA-WH1 toxicity in bacteria: a primary hit of damage to the membrane, compromising bionergetics, triggers a stroke of oxidative stress, which is exacerbated due to the aggregation-dependent inactivation of enzymes and transcription factors that enable the cellular response to such injury. The proteinopathy caused by the prion-like protein RepA-WH1 in bacteria recapitulates some of the core hallmarks of human amyloid diseases.